Women and corruption - Akhmetova, Elmira (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
ransparency International, the global coalition against corruption, defines corruption as “the abuse of entrusted power for private gain. It hurts everyone who depends on the integrity of people in a position of authority.”Corruption has a devastating impact on the social, economic, ethical and mental wellbeing of human beings as an individual and community. In Islam, any form of corruption (fasÉd) like bribery, extortion, kickback and illegal gratuity are strictly prohibited by the texts.